2017
DOI: 10.1039/c6ra25774g
|View full text |Cite
|
Sign up to set email alerts
|

Thermally robust: triarylsulfonium ionic liquids stable in air for 90 days at 300 °C

Abstract: Select triarylsulfonium salts are ionic liquids with outstanding long-term, high-temperature aerobic stability (no mass loss in 90 days at 300 °C in air), making them among the most thermally stable organic materials known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…The chemical names and molecular structures of the ILs examined in this study are shown in Table 1. ILs 1-2 were prepared using previously reported methods [27][28][29]. NMR spectra were recorded on a 500 MHz JEOL spectrometer using CDCl 3 as a solvent at room temperature.…”
Section: Synthesis Of Ionic Liquidsmentioning
confidence: 99%
“…The chemical names and molecular structures of the ILs examined in this study are shown in Table 1. ILs 1-2 were prepared using previously reported methods [27][28][29]. NMR spectra were recorded on a 500 MHz JEOL spectrometer using CDCl 3 as a solvent at room temperature.…”
Section: Synthesis Of Ionic Liquidsmentioning
confidence: 99%
“…So far, the thermal stability of ILs has been studied by many techniques, such as UV (ultraviolet)-vis spectroscopy [36], flame ionization detection (FID) [37,38], and mass spectrometry (MS) [39][40][41]. Moreover, in some studies, ILs are heated isothermally in a furnace and open to air to simulate the real environment [42,43]. In order to quantitatively evaluate the thermal stability of ILs, parameters accounting for short-term and long-term thermal stability are obtained by thermogravimetric analysis (TGA), and the most representative ones are the onset decomposition temperature Tonset and Tz/y (decomposition degree z in a selected time y), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to common descriptions of ILs as being thermally stable, most begin to slowly decompose around 250 C. 37 The use phosphonium and sulfonium cations comprised of peraryl groups, however, have shown exceptional thermal stability, upwards of 300 C for a period of 3 months. [38][39][40] While many of these ILs do not melt below 100 C, these mesothermal ILs have shown a lot of promise as heat transfer uids, lubricants, solvents, and catalysts for high temperature reactions. 41 Despite the connement to thermally stable groups, innovative ways have been developed to expand this design space [42][43][44] and even tune the melting point.…”
Section: Introductionmentioning
confidence: 99%